Ciprofloxacin Affect Sperm Quality and Induced Testicular and Hepatic Injury in Male Mice - Sasi, Samira; Al ghoul, Nagia; Sumaia Toumi; Nuri Awayn; Walid Saadawi; Ragil Prastiya (AlQalam Journal of Medical and Applied Sciences, 2024)
Ciprofloxacin (CPFx) is one of a second-generation fluoroquinolones antibiotic and is prescribed a lot for curing bacterial infection. The aim of this study was to investigate of impact CPFx on sperm characteristics, liver DNA and histological structure of liver and testes. Twenty-four male mice aged 7-10 weeks were divided into three groups of eight. The first group (control) was given distilled water. The second and third groups received CPFx with doses 500 and 750 mg/kg respectively. All treatments were administrated orally for 14 days. Three untreated females were put with one treated male for mating. At the end of dosing period, mice were killed, testes and liver were removed and weighed. Sperm parameters, testosterone level and liver DNA were measured. Histopathology of liver and testes was carried out. The results showed that CPFx significantly affected liver DNA, sperm motility and morphology as well as it caused histopathological alterations of hepatic and testicular tissues. Moreover, it led to a significant elevation in the percentage of dead fetuses and also deformity fetuses. The results indicate that CPFX has detrimental effects on sperm quality, liver DNA and histological structure of testes and liver; therefore, it should be used with great caution. سيبروفلوكساسين هو أحد المضادات الحيوية من الجيل الثاني من مجموعة الفلوروكينولون ويوصف كثيرًا لعلاج العدوى البكتيرية. كان الهدف من هذه الدراسة هو التحقيق في تأثير سيبروفلوكساسين على خصائص الحيوانات المنوية وحمض الكبد والبنية النسيجية للكبد والخصيتين. تم تقسيم أربعة وعشرين فأرًا ذكرًا تتراوح أعمارهم بين 7 و10 أسابيع إلى ثلاث مجموعات من ثمانية. المجموعة الأولى (الضابطة) أعطيت ماء مقطر. المجموعة الثانية والثالثة أعطيت سيبروفلوكساسين بجرعات 500 و 750 ملغ / كغ على التوالي. تم إعطاء جميع المعالجات عن طريق الفم لمدة 14 يومًا. تم وضع ثلاث إناث غير معالجة مع ذكر معالج للتزاوج. في نهاية فترة الجرعات، تم قتل الفئران وإزالة الخصيتين والكبد ووزنها. تم قياس معايير الحيوانات المنوية ومستوى هرمون التستوستيرون والحمض النووي للكبد. تم إجراء فحص نسيجي للكبد والخصيتين. أظهرت النتائج أن سيبروفلوكساسين أثر بشكل كبير على الحمض النووي للكبد وحركة الحيوانات المنوية وشكلها بالإضافة إلى أنه تسبب في حدوث تغيرات نسيجية مرضية في أنسجة الكبد والخصيتين. علاوة على ذلك، أدى إلى ارتفاع كبير في نسبة الأجنة الميتة وكذلك الأجنة المشوهة. تشير النتائج إلى أن سيبروفلوكساسين له تأثيرات ضارة على جودة الحيوانات المنوية والحمض النووي للكبد والبنية النسيجية للخصيتين والكبد؛ لذلك، يجب استخدامه بحذر شديد